ANALISIS AFIKSASI DALAM ALBUM “DEKADE” LAGU AFGAN - Aulia Zahra Fadhila (Jurnal Ilmiah Langue and Parole, 2020)
The research conducted was entitled "Affixation Analysis in the DEKADE Afgan Song Album". This research was conducted using qualitative methods. The data used in the study were taken from the lyrics of the Afgan song on the album "DEKADE" which is available on sites on the internet. The problem discussed was the use of affixes to Afgan's song lyrics in DEKADE's album. The results of the research conducted show that there are many uses of affixation in the lyrics of agu Afgan. There are 112 words that contain affixations in the Afgan song lyrics on the album. Of the 112 data found with affixes, suffixes had the highest percentage of usage. There were 69 data suffixes that were found, consisting of the suffixes kan-, -nya, -an, and -i. The suffix that is mostly found is kan-, while the suffix with the smallest frequency of occurrence is the suffix -an. Like suffixes, prefixes are also found in the lyrics of the song. The prefix found in 24 data consisted of tar, ber-, di-, mem-, and se-. Meanwhile, in the confixes of the song lyrics, there are 9 data consisting of performances and occasional data.